Phenylketonuria: Brain Phenylalanine Concentrations Relate Inversely to Cerebral Protein Synthesis. Issue 2 (February 2015) - de Groot, Martijn J; Sijens, Paul E; Reijngoud, Dirk-Jan; Paans, Anne M; van Spronsen, Francjan J
In phenylketonuria, elevated plasma phenylalanine concentrations may disturb blood-to-brain large neutral amino acid (LNAA) transport and cerebral protein synthesis (CPS). We investigated the associations between these processes, using data obtained by positron emission tomography withl -[1- 11 C]-tyrosine ( 11 C-Tyr) as a tracer. Blood-to-brain transport of non-Phe LNAAs was modeled by the rate constant for 11 C-Tyr transport from arterial plasma to brain tissue (K1 ), while CPS was modeled by the rate constant for 11 C-Tyr incorporation into cerebral protein (k3 ). Brain phenylalanine concentrations were measured by magnetic resonance spectroscopy in three volumes of interest (VOIs): supraventricular brain tissue (VOI 1), ventricular brain tissue (VOI 2), and fluid-containing ventricular voxels (VOI 3). The associations between k3 and each predictor variable were analyzed by multiple linear regression. The rate constant k3 was inversely associated with brain phenylalanine concentrations in VOIs 2 and 3 (adjusted R 2 =0.826, F =19.936, P =0.021). Since brain phenylalanine concentrations in these VOIs highly correlated with each other, the specific associations of each predictor with k3 could not be determined. The associations between k3 and plasma phenylalanine concentration, K1, and brain phenylalanine concentrations in VOI 1 were nonsignificant. In conclusion, our study shows an inverse association between k3 and increased brain phenylalanine concentrations.